Meningkatkan Kepercayaan Diri Melalui Konseling Direktif Dengan Teknik Pendekatan Cbt (Cognitive Behavior Therapy) - Wahyu Aulizalsini Alurmei; Salsabila Putri Azzahra; Vanesa Kusuma Dewi; Kurnia Nurul Azmi; Ananda Intan Fadhillah Yahya (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research aims to assess the effect of employing cognitive behavior therapy (CBT) counseling on enhancing the self-assurance levels among 19-25-year-old students enrolled at the Faculty of Psychology, Bhayangkara University of Greater Jakarta. The study utilized a quantitative methodology, employing questionnaires for data collection. The collected data revealed that among 30 students, 4 exhibited low self-confidence levels. These four individuals were chosen as subjects for the research, receiving CBT-based counseling to address their self-confidence issues. The focus of the researchers was solely on interventions targeting self-confidence problems through CBT counseling techniques. The counseling sessions uncovered that these students faced challenges in feeling confident when interacting with groups of people, experiencing worry and a lack of assurance in such situations. While the outcomes of the counseling using CBT did not achieve a complete 100% enhancement in the self-confidence levels of the students at the Faculty of Psychology, Bhayangkara University of Greater Jakarta, there were observable positive changes in the students' perspectives and their ability to manage their thoughts. The efficacy of the counseling could be deemed successful with a 70% success rate.